2022
DOI: 10.21037/jtd-21-1664
|View full text |Cite
|
Sign up to set email alerts
|

Immune checkpoint inhibitors in neoadjuvant therapy of non-small cell lung cancer: a systematic review and meta-analysis

Abstract: Background: Our objective was to explore the safety and feasibility of immune checkpoint inhibitors (ICIs) in the neoadjuvant treatment of non-small cell lung cancer (NSCLC).Methods: Embase, PubMed and Web of Science were systematically searched from 1 st January 2018 to 1 st August 2021 for studies with data on the treatment-related adverse reactions (TRAE), immune-related adverse events (irAE), perioperative information, major pathological response (MPR), pathologic complete remission (pCR) and objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…The safety and efficacy of neoadjuvant immunotherapy for cancer treatment is an area of active research . In locally advanced esophageal cancer, the addition of immunotherapy to standard chemoradiotherapy prior to esophagectomy did not increase 30-day major complications (including readmission rate and mortality) .…”
Section: Discussionmentioning
confidence: 99%
“…The safety and efficacy of neoadjuvant immunotherapy for cancer treatment is an area of active research . In locally advanced esophageal cancer, the addition of immunotherapy to standard chemoradiotherapy prior to esophagectomy did not increase 30-day major complications (including readmission rate and mortality) .…”
Section: Discussionmentioning
confidence: 99%
“…3 Meanwhile, Ge et al conducted that neoadjuvant chemoimmunotherapy achieved more pathological relief in NSCLC but caused higher treatment-related adverse events (TRAEs) and postoperative complications than neoadjuvant immune checkpoint inhibitors (ICIs) only. 5 Neoadjuvant chemoimmunotherapy brings a new era to surgical treatment for patients with NSCLC. The neoadjuvant chemoimmunotherapy has brought efficacy and survival benefits, but the TRAEs and wound complications have still not stated clearly.…”
Section: Introductionmentioning
confidence: 99%
“…Neoadjuvant regimens revolutionized the treatment and increase both locoregional and systemic control, especially for immunotherapy plus chemotherapy. A meta-analysis concluded that neoadjuvant immunotherapy combined with chemotherapy achieved more pathological relief, but TRAEs and postoperative complications were also increased [ 7 ]. A meta-analysis in 2022 reported that neoadjuvant immunotherapy or chemoimmunotherapy was safe and effective in stage I–III NSCLC, and compared with neoadjuvant immunotherapy, neoadjuvant chemoimmunotherapy significantly improved the rate of pathological response without increasing SAEs or delaying surgery [ 8 ].…”
Section: Introductionmentioning
confidence: 99%